Study of Boron Complexation with Pyridoxine: Effect of Interaction Time, Temperature, and Amount of Pyridoxine - Nurlisa Hidayati; Ariqah Fianti; Mita Arnela (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2023)
Borax is one of the compounds of boron (B), which is widely used as an anti-fungal, wood preservative, and antiseptic in cosmetics. Boron can form complexes with biomolecules such as pyridoxine, so it is interesting to know the interaction between borax and pyridoxine. This study seeks to investigate the complexation of boron, which is obtained from borax, with pyridoxine under various conditions of time, temperature, and the amount of pyridoxine. The resulting complex was characterized by UV-Vis spectrophotometry, Fourier Transform Infrared (FT-IR), and X-Ray diffraction (XRD). The study was initiated by optimizing the complexation of boron and pyridoxine. The maximum wavelengths of pyridoxine were found in the 205 nm and 292 nm regions, while the boron-pyridoxine complex was found in the 237 nm region. The obtained contact time, temperature, and amount of pyridoxine are 40 minutes, 60 Â°C, and 2 mL respectively. The results of the Fourier transform infrared (FT-IR) analysis of the boron-pyridoxine complex showed that there were OH groups, aromatic C=C groups, aliphatic C-C groups, B-H groups, and B-O groups. The results of the XRD analysis of the boron-pyridoxine complex obtained a diffraction angle of 30.93Â°.